Triple Invariant Point Theorems with PPF Dependence for Contractive Type Mappings - Rathee, Savita; Kumari, Neelam (Communications in Mathematics and Applications, 2022)
In this paper, some results concerning the existence and uniqueness of triple invariant point with PPF dependence for non linear mapping in partially ordered complete metric spaces using the domain space \(C[[a,b],E]\) that is distinct from the range \(E\). Our results generalize and extend recent coupled invariant point theorems with PPF dependence founded by Drici et al. (Fixed point theorems in partially ordered metric spaces for operators with PPF dependence, Nonlinear Analysis 67 (2007), 641 – 647).